Potentiality of petrochemical wastewater as substrate in microbial fuel cell - Sarmin, Sumaya; Asmida, Ideris; Ethiraj, Baranitharan; Amirul Islam, Mohammad; Chin, Sim Yee; Khan, Md. Maksudur Rahman (Institute of Physics Publishing, 2020)
The petrochemical wastewater (PCW) from acrylic acid plant possesses very high chemical oxygen demand (COD) due to presence of acrylic acid along with other organic acids. The treatment of PCW by conventional methods is energy intensive. The treatment of PCW with concurrent power generation by employing microbial fuel cell (MFC) could be a potential alternative solving the problem of energy and environment. The goal of the present paper is to evaluate the viability of treating the wastewater using anaerobic sludge as biocatalyst in a dual- chamber MFC for simultaneous power generation and wastewater treatment. This study demonstrates that anaerobic sludge (AS) could work as a biocatalyst producing maximum power density of 0.75 W/m3at current density and open circuit voltage (OCV) of 412 mA/m2 and 0.45 V respectively using PCW with an initial COD of 45,000 mg/L. The COD removal efficiency and the columbic efficiency (CE) were found 40% and 13.11%, respectively. The mechanism of electron transfer in the anode was analyzed by cyclic voltammetry (CV) and the resistances across the electrode/biofilm/solution interface were investigated by employing impedance spectroscopy (EIS). The current work proves the capability of the MFC for the treatment of acrylic acid plant PCW using anaerobic sludge (AS) as biocatalyst.